Carbon Nanosheet Anode for Sodium‐Ion Storage and Its Application in Sodium‐Ion Hybrid Capacitors. Issue 19 (20th May 2020) - Chen, Li; Duan, Wenhui; Yang, Bingjun; Liu, Bao; Li, Hongxia; Lang, Junwei; Chen, Jiangtao
Abstract: In this study, sodium ion hybrid capacitors (SIHCs) constructed by using battery‐type carbon nanosheet (CNS) as anode and capacitive activated carbon (AC) as cathode are reported. The CNSs with large interlayer spacing were deposited on Na2 CO3 powder by using chemical vapor deposition method. The CNS anode for sodium ion storage exhibits outstanding rate capability (138 mAh g −1 at 10 A g −1, 63 % retention of the capacity at 0.05 A g −1 ) and excellent long‐term cyclability at 10 A g −1 after 12500 cycles. Benifting from high performance of anodes abovemensioned, the assembled SIHC based on CNS and AC, operated in a voltage window of 1.0∼4.0 V, delivers a high specific energy of 135 Wh kg −1 at 250 W kg −1 and a maximum power of 25 kW kg −1 with the output 69 Wh kg −1 . Abstract : The carbon nanosheets (CNSs) have been prepared by chemical vapor deposition method using Na2 CO3 as template and CNSs anode displays high rate performance as well as excellent long‐term cyclability. The sodium ion hybrid capacitors (SIHCs) have been constructed by using battery‐type CNSs as anode and capacitive activated carbon as cathode. And the optimized SIHC device delivers a high energy density of 135 Wh kg −1 and a maximum power output of 25 kW kg −1 .